The relationship between self-efficacy, work engagement and inner motivation with teacher's job performance - کریم سواری; Maryam Falahi; Noreyeh Zayerchi (Allameh Tabataba'i University Press, 2017)
The Purpose Of This Study Was To Investigate The Relationship Between Self‌Efficacy, Work Engagement And Inner Motivation With Teacher's Job Performance. The Statistical Population Of This Research Was All Teachers Of Shadegan City In 1395,Numbering About 540 People.The Statistical Sample In This Research Was A Random Sampling Method And 200 teachers From The Morgan Table Were Selected. The Instruments Used In This Study Were Sherer Self-Efficacy Inventory (1999) Utrecht's Job Passion(2002),Carrie's Internal Motivation (2012), And Paterson's (2000) Job Performance Questionnaire.This Research Is Work In Terms Of The Component Part Of The Research And In Terms Of Implementation It Is A Part Of Correlation Research.The Results Of This Study Showed That There Is A Significant Positive Correlation Between Self-Efficacy And Teacher's Job Performance Using Pearson Correlation Coefficient And Regression.There Is A Significant Positive Relationship Between Work Engagement And Teacher's Job Performance.There Is A Significant Positive Correlation Between The Internal Motivation And The Teacher's Job Performance The Self-Efficacy Variable With A Beta Coefficient Of 38%, Job-Seeking Variables With A Beta Coefficient Of 32%, And An Internal Motivation Variable With A Beta Coefficient Of 29% Can Positively And Significantly Predict The Performance Of The Teachers.